Spesies Nematoda Puru Akar (Meloidogyne spp.) yang Berasosiasi dengan Penyakit Umbi Bercabang pada Wortel: Penyakit Baru di Indonesia - . Supramana; Gede Suastika (Jurnal Ilmu Pertanian Indonesia, 2012)
Diseases and pests is one of the main obstacles in the cultivation of carrots in Indonesia. One of the emerging diseases that cause significant losses is branched (forked) tuber caused by root knot nematodes (RKN), Meloidogyne spp. Research aimed to identify the species of RKN was carried out by taking samples of diseased plants and soil from the carrot plantation in four vegetable production centers on the island of Java, namely: (1) District Pacet, Cianjur, West Java, (2) Dieng Plateau, Central Java, (3) Kopeng, Central Java and (4) District Bumiaji, Kota Batu, East Java. Three carrot plantations with different altitude / elevation were sampled for each area involved. NPA species identification was done by observation of perineal pattern (fingerprint-like pattern) of females and PCR of nematodes r-DNA ITS. Four Meloidogyne species, namely M. arenaria, M. hapla, M. incognita, and M. jananica, were identified from West Java, Central Java and East Java samples, whereas M. fallax found only in West Java.